2022
DOI: 10.23887/ijssb.v6i3.40508
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Literature and Financial Technology on Financial Inclusion Among Accounting Student

Dhany Efita Sari,
Erlin Ade Selviana,
Brilliani
et al.

Abstract: Improvements in financial literacy serve as the primary driver of financial inclusion. To avoid financial difficulties, everyone should be financially literate. Having better financial literacy increases one's chances of enjoying life's pleasures while also being well-funded. This study aims to analyze the effect of financial literacy and financial technology on financial inclusion. The population in this study consisted of 180 accounting students. This study was a causal comparative research, and the data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Research by Prasad et al (2018), Rahayu and Putra (2019), A. Detunji and David West (2019), Morgan, P. J., & Long, T. Q. ( 2020), Shen, Hueng, and Hu (2020), Sari et al (2022) found that financial literacy has a positive impact on financial inclusion.…”
Section: The Impact Of Financial Literacy On Financial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Prasad et al (2018), Rahayu and Putra (2019), A. Detunji and David West (2019), Morgan, P. J., & Long, T. Q. ( 2020), Shen, Hueng, and Hu (2020), Sari et al (2022) found that financial literacy has a positive impact on financial inclusion.…”
Section: The Impact Of Financial Literacy On Financial Inclusionmentioning
confidence: 99%
“…Additionally, studies conducted by Sennou, Outtara, and Acclassato Houensou (2019); Makina, D. (2019); P.K. Ozili (2020); Sari et al, 2022 found that financial technology has an impact on financial inclusion.…”
Section: The Impact Of Financial Literacy On Financial Inclusionmentioning
confidence: 99%